2018
DOI: 10.1007/s00167-018-4939-x
|View full text |Cite
|
Sign up to set email alerts
|

In-vivo three-dimensional MR imaging of the intact anterior cruciate ligament shows a variable insertion pattern of the femoral and tibial footprints

Abstract: 3D imaging of the ACL footprints reveals a distinct difference in insertion site morphology and fiber bundle orientation between the femoral and tibial footprint. This questions the concept of strict anatomical separation of the ACL into an anteromedial and posterolateral bundle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 20 publications
0
26
0
Order By: Relevance
“…In our study orthopedic surgeons were able to determine the same point (femoral footprint) with a mean difference of 2.97 mm between two assessments of 20 scans. A high diversity in the size and shape of the femoral footprint has been reported [ 12 ], and this footprint appears to be ribbon shaped with a length of 16 mm and a width of 8 mm [ 11 , 12 ]. In this light, a mean 3D difference of 2–5 mm can be regarded acceptable.…”
Section: Discussionmentioning
confidence: 99%
“…In our study orthopedic surgeons were able to determine the same point (femoral footprint) with a mean difference of 2.97 mm between two assessments of 20 scans. A high diversity in the size and shape of the femoral footprint has been reported [ 12 ], and this footprint appears to be ribbon shaped with a length of 16 mm and a width of 8 mm [ 11 , 12 ]. In this light, a mean 3D difference of 2–5 mm can be regarded acceptable.…”
Section: Discussionmentioning
confidence: 99%
“…24 Additional oblique scans in the coronal and axial planes improve visualization of the ACL, and a 3-dimensional MRI sequence might provide more information on the ACL rupture characteristics. 1,12,20,22,25,26 Furthermore, it has been reported that MRI performed with the knee in flexion instead of extension improves accuracy in the diagnosis of partial and complete ACL ruptures in general. Although not investigated, this might improve the accuracy of MRI for classifying the characteristics of complete ACL rupture that were investigated in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…During the past few years, an effort has been made to understand the precise anatomy of the ACL footprints on the tibial and femoral sides by using 3D MRI and computed tomography scans to improve tunnel position and, eventually, clinical outcomes. 1,12,14,24,31 33 In a cadaveric study by Han et al, 12 it was demonstrated that 3D MRI localization of the femoral and tibial footprints of the ACL is comparable with open dissection. Using the same 3D MRI technique, Hart et al 14 evaluated the tunnel positions that were created by 4 different orthopaedic sport surgeons for a series of patients in comparison with the native ACL footprint of the patients.…”
Section: Discussionmentioning
confidence: 99%